Creating individual level air pollution exposures in an anonymised data safe haven: a platform for evaluating impact on educational attainment - Mizen, Amy; Lyons, Jane; Doherty, Ruth; Berridge, Damon; Wilkinson, Paul; Milojevic, Ai; Carruthers, David; Akbari, Ashley; Lake, Iain; Davies, Gwyneth; Mavrogianni, Anna; Al Sallakh, Mohammad; et al. (International Journal of Population Data Science, 2018)
Introduction There is a lack of evidence on the adverse effects of air pollution on cognition for people with air quality-related health conditions. We propose that educational attainment, as a proxy for cognition, may increase with improved air quality. This study will explore whether asthma and seasonal allergic rhinitis, when exacerbated by acute exposure to air pollution, is associated with educational attainment. Objectives To describe the preparation of individual and household-level linked environmental and health data for analysis within an anonymised safe haven. Also to introduce our statistical analysis plan for our study: COgnition, Respiratory Tract illness and Effects of eXposure (CORTEX). Methods We imported daily air pollution and aeroallergen data, and individual level education data into the SAIL databank, an anonymised safe haven for person-based records. We linked individual-level education, socioeconomic and health data to air quality data for home and school locations, creating tailored exposures for individuals across a city. We developed daily exposure data for all pupils in repeated cross sectional exam cohorts (2009-2015). Conclusion We have used the SAIL databank, an innovative, data safe haven to create individual-level exposures to air pollution and pollen for multiple daily home and school locations. The analysis platform will allow us to evaluate retrospectively the impact of air quality on attainment for multiple cross-sectional cohorts of pupils. Our methods will allow us to distinguish between the pollution impacts on educational attainment for pupils with and without respiratory health conditions. The results from this study will further our understanding of the effects of air quality and respiratory-related health conditions on cognition. Highlights This city-wide study includes longitudinal routinely-recorded educational attainment data for all pupils taking exams over seven years; High spatial resolution air pollution data were linked within a privacy protected databank to obtain individual exposure at multiple daily locations; This study will use health data linked at the individual level to explore associations between air pollution, related morbidity, and educational attainment.